The weeping tide - Foody, Amanda (Foody, Amanda. Wilderlore, 2022)
Lore Keeper apprentice Barclay helps his teacher investigate a carnivorous algae bloom and its possible connection to recurring attacks by the Legendary Beast of the Sea.